Emerging Supranormal Wilderness. Encountering Sites of Folk Belief in Finnish Belief Narratives and in the Field - Björkman John (Kungliga Gustav Adolfs Akademien för svensk folkkultur, 2026)
Finnish belief narratives from the late nineteenth and early twentieth centuries contain a wealth of descriptions of supernatural or rather supranormal encounters and interactions taking place at specified, often identifiable places. Such encounters are typically set in areas regarded by contemporaries as wilderness, an environment which in folk belief is typically viewed as unpredictable and unruly. The belief narratives can be seen to express the agency of such unruly environments. The narratives express a worldview in which the wilderness is seen as an agent, which can emerge into different types of interaction with people at specific wilderness sites. This study looks at eighty sites mentioned as places of supranormal wilderness encounters in belief narratives. Ways in which the agency of a place is described in the narratives are compared with first-hand experiences from vis-iting the sites in person. Field visits to the same sites today show that a person’s cultural conditioning clearly affects how the place is experienced, but also that places known for supranormal interaction can give rise to experiences similar to the ones expressed in the narratives.